Mechatronic Systems: Theory and Applications Proceedings of the Second Workshop on Mechatronic Systems JSM'2014 - Abbes, Mohamed Slim; Choley, Jean-Yves; Chaari, Fakher; Jarraya, Abdessalem; Haddar, Mohamed (Lecture Notes in Mechanical Engineering, 2014)
The book offers a snapshot of the state-of-art in the field of model-based mechatronic system design. It covers topics including machine design and optimization, predictive systems in manufacturing networks, and the development of software for modeling and simulation of processes, which are supplemented by practical case studies. The book is a collection of fifteen selected contributions presented during the Workshop on Mechatronic Systems, held on March 17-19, 2014, in Mahdia, Tunisia. The workshop was jointly organized by the Laboratory of Mechanics Modeling and Production (LA2MP) of the National School of Engineers Sfax, Tunisia, and the Laboratory for Mechanical Systems and Materials Engineering (LISMMA) of Higher Institute of Mechanics (SUPMECA), Paris, France.